2011
DOI: 10.1016/j.freeradbiomed.2010.10.689
|View full text |Cite
|
Sign up to set email alerts
|

Marked changes in endogenous antioxidant expression precede vitamin A-, C-, and E-protectable, radiation-induced reductions in small intestinal nutrient transport

Abstract: Rapidly proliferating epithelial crypt cells of the small intestine are susceptible to radiationinduced oxidative stress, yet there is a dearth of data linking this stress to expression of antioxidant enzymes and to alterations of intestinal nutrient absorption. We previously showed that 5 -14 d after acute γ-irradiation, intestinal sugar absorption decreased without change in antioxidant enzyme expression. In the present study, we measured antioxidant mRNA and protein expression in mouse intestines taken at e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 45 publications
(62 reference statements)
2
19
0
Order By: Relevance
“…Intestinal uptake rates were determined as described previously (45,46). Briefly, 1-cm segments of the proximal small intestine were individually mounted and everted on grooved steel rods.…”
Section: Methodsmentioning
confidence: 99%
“…Intestinal uptake rates were determined as described previously (45,46). Briefly, 1-cm segments of the proximal small intestine were individually mounted and everted on grooved steel rods.…”
Section: Methodsmentioning
confidence: 99%
“…The nonmetabolizable glucose analog, 3-O-methylglucose, is absorbed by the same transporter mediating D-glucose uptake, and their comparative uptake rates are often used to distinguish effects on membrane transport from those on glucose metabolism in the cytosol (3). Our studies have shown that transport rates of these nutrients are affected differently when mice are exposed to acute doses of low-LET 137 Cs gamma rays (4, 5). However, the effect of chronic irradiation on nutrient transport is not known and agents to prevent or mitigate such reductions have not been assessed.…”
Section: Introductionmentioning
confidence: 85%
“…A combination of vitamins A, C and E reduced bone marrow toxicity caused by radioimmunotherapy with 131 I-labeled antibodies (10). Furthermore, we have demonstrated a diet enriched in vitamins A, C and E (vitamin ACE) protects intestinal transport of these nutrients under acute irradiation conditions (4). …”
Section: Introductionmentioning
confidence: 99%
“…This dose can be as high as 30-40% of the total dose deposited by an HZE particle (62,101,209). However, a particles emitted from common radioactive sources (e.g., 238 Pu or 241 Am) used for cellular experiments do not pose such problems. Interpretations of the apparent nontargeted effects are relatively straightforward as these a particles do not produce secondary radiations that crossirradiate neighboring cells (126).…”
Section: Hze Particles and Generation Of Secondary Radiationsmentioning
confidence: 99%
“…Earlier studies indicated that nutrient absorption in mice was significantly reduced following the exposure to c rays (217,239). Decreases in intestinal sugar absorption were associated with a rapid decrease in SOD and catalase abundance, followed by dramatic upregulation within 4 h and then downregulation a few days later (238).…”
mentioning
confidence: 95%